Metastatic cutaneous apocrine adenocarcinoma successfully treated with systemic anti‐androgen therapy—A case report - Collette, Fanny (Clin Case Rep, 2020)
Primary cutaneous apocrine adenocarcinoma (PCAC) is an extremely rare neoplasm involving the sweat glands. Due to a lack of cases, there is no consensus for the systemic treatment of locally advanced or metastatic PCAC. Anti‐androgen therapy may have activity in inoperable or metastatic PCAC with high androgen receptor (AR) expression.